Acoustic analysis of a flute-like silence. (26th May 2021) - Zhao, Xiaochen; Tan, Hao; Li, Shang
Highlights: A two-dimensional analytical method for flute-like silencer is developed. Based on this method, the optimal design of a flute-like silencer is achieved. The acoustic performance was also measured to validate the theoretical model. Abstract: The passive control of low-frequency duct noise remains a technical challenge. Herschel-Quincke (HQ) tube is effective in low frequency noise reflection. Previous studies showed that, when the bypass of the HQ tube is filled with a lighter gas and covered by tensioned membranes, the HQ tube becomes a flute-like silencer [L.Huang, Attenuation of low frequency duct noise by a flute-like silencer, Journal of Sound and Vibration 326 (2009) 161–176]. Another resonance occurs and the transmission loss spectrum can keep a desirable high level. In this paper, a two-dimensional analytical method for flute-like silencer is developed and this method offers an effective way in acoustic calculations with variable parameters. The details of the modal behavior are analyzed and a parametric study is conducted to obtain optimal design. It shows that the noise attenuation mechanism can be interpreted as destructive interference and the resonance of a single spring-mass system. The trends of the experimental results and theoretical calculations are in good agreement, however, significant deviations in absolute value are observed around the second peak of the transmission loss. Minimizing sound and gas leakage is still an issue that needs to be considered. The effects of cavity filling with different gases are also investigated and it is found that the use of hydrogen can bring performance improvement in low-frequency range. After the introduction of another stretched membrane, the optimal logarithmic bandwidth of the silencer can be further extended to about 5.2.